Effects Of Rotation On Auditor Independence And Quality Of Audit Service In Malaysian Banking IndustryThis study highlights the nature of auditor rotation in the Malaysian banking industry and its effects on auditor independence and quality of audit se (Issues in Social and Environmental Accounting (ISEA), 2012)
This study highlights the nature of auditor rotation in the Malaysian banking industry and its effects on auditor independence and quality of audit service in the industry. To generate primary data for analysis, interviews were conducted on officials of two banking institutions and one accounting/audit firm. The study finds that there have not been significant changes in the annual appointment of auditors in the Malaysian banking institutions over the last ten years, suggesting that there is a good working relationship between the auditors (especially the Big4) and the banks. This allows room for continuous debate on the need for mandatory rotation as a means for ensuring auditor independence and high audit quality in the Malaysian banking industry. In the absence of statutory/mandatory requirement for auditor rotation, it is recommended that the Malaysian banking institutions should be carefully evaluating the impact auditor rotation would have on the quality of audit work on their current and future financial statements, as they decide whether to rotate their auditors or not.